Kajian Yuridis Terhadap Peran Justice collaborator dalam Sistem Peradilan Pidana untuk Perkara Narkotika dengan Ancaman Hukuman Mati - Nurhadi, Syarif; Rahmat, Diding; Sudarto, Sudarto (Neolectura, 2024)
The increase in drug abuse among adults has been rising significantly. This can be observed through reports in electronic and print media, which daily cover the arrests of drug abusers. Authorities responsible for combating drug abuse include the National Narcotics Agency and the Indonesian National Police. Internationally, there are several conventions governing the use and distribution of narcotics issued by global organizations such as the United Nations, including the Single Convention on Narcotic Drugs 1961 (United Nations Conference for Adoption of a Single Convention on Narcotic Drugs 1961), the Convention on Manufacture and Distribution of Narcotic Drugs (Geneva 1931), and the Convention for the Suppression of Illicit Traffic in Dangerous Drugs (Geneva 1936). Furthermore, it is important to note that drug traffickers involved in the production, import, export, or distribution of Class I and II Narcotics can face the death penalty if the amount of narcotics distributed exceeds certain limits. The death penalty can also be applied to traffickers who engage in activities such as offering narcotics for sale, selling, purchasing, receiving, acting as an intermediary in transactions, exchanging, or delivering Class I and II Narcotics when the quantity exceeds a specified amount. In relation to law enforcement efforts, the term justice collaborator refers to a criminal offender who is willing to cooperate with law enforcement to expose certain organized criminal cases that pose a serious threat. These offenses include corruption, terrorism, narcotics, money laundering, human trafficking, and other organized crimes. In Supreme Court Circular (SEMA) Number 4 of 2011, a justice collaborator is also referred to as a cooperating witness.